Motioning the politics of security: The primacy of movement and the subject of security - Huysmans, Jef (Security dialogue, 2022)
The article explores challenges that giving conceptual primacy to movement poses for thinking the politics of security. In security studies, there has been an intense interest in mobile phenomena and the nature of security techniques that seek to control, contain or steer them. However, when exploring how these mobile phenomena bear upon conceptions of politics and their contestation, the analytics tend to turn back to more static or sedentary categories and reference points. Against this background, the article develops an analytical framework for security and its politics that gives conceptual primacy to movement. Giving conceptual primacy to movement implies three key moves: (a) changing lines from enclosures and connectors to pathways; (b) shifting from understanding movement through positions and nodes to the continuity of movement; and (c) displacing architectural and infrastructural readings of the relations between movements with readings of continuously unfolding confluences of movements moving in relation to one another. Applying these three moves displaces conceptions of movement as border crossings and networked connections with the notion of entangling movements moving in relation to one another. One of the implications for security studies is that taking such a point of view challenges the use of ‘the subject of security’, understood in terms of state sovereignty and the positioning of differential security claims hooked into group identity, as a key device for making security politically meaningful and contested. The article concludes that giving conceptual primacy to movement invites security studies not to limit itself to studying the politics of movement but to also incorporate a motioning of politics.